(untitled) - Pavlovská, Michaela (Romanica Olomucensia, 2011)
This article focuses on analysis of the main character Virgínia of the novel The Marble Dance (Ciranda de pedra, 1954) written by Brazilian author Lygia Fagundes Telles (1923) who uses the form of Bildungsroman to show the protagonist's search for her identity. The novel constitutes an alternative to the traditional male novels of formation which contributes to the reformulation of this genre. This way Fagundes Telles introduces a new dynamic heroin who has to gain her "Bildung" on her own and who represents a modern attitude of a female individual toward the world.
Keywords: Lygia Fagundes Telles; Bildungsroman; female protagonist; identity.